2007
DOI: 10.1111/j.1567-1364.2006.00161.x
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity ofSaccharomycesyeast strains from grape berries of wine-producing areas using starter commercial yeasts

Abstract: The use of commercial wine yeast strains as starters has grown extensively over the past two decades. In this study, a large-scale sampling plan was devised over a period of 3 years in three different vineyards in the south of France, to evaluate autochthonous wine yeast biodiversity in vineyards around wineries where active dry yeasts have been used as fermentation starters for more than 5 years. Seventy-two spontaneous fermentations were completed from a total of 106 grape samples, and 2160 colonies were iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
83
1
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(93 citation statements)
references
References 27 publications
5
83
1
4
Order By: Relevance
“…The impact of commer- cial strains on the diversity of endogenous wine yeast strains is still controversial, since some authors have shown that the use of active dry yeasts reduced the variability of wine cellar strains (14), whereas other studies did not evidence any impact (6,12,53). In this study, only 7% of cellar strains were found to be related to 4 commercial strains usually used in sweet and dry white wine making in the Bordeaux region for over 25 years.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…The impact of commer- cial strains on the diversity of endogenous wine yeast strains is still controversial, since some authors have shown that the use of active dry yeasts reduced the variability of wine cellar strains (14), whereas other studies did not evidence any impact (6,12,53). In this study, only 7% of cellar strains were found to be related to 4 commercial strains usually used in sweet and dry white wine making in the Bordeaux region for over 25 years.…”
Section: Discussionmentioning
confidence: 45%
“…A highly discriminating method based on 15 microsatellite markers specific to S. cerevisiae was used for molecular typing at the strain level. In comparison to previous studies based on other methods, such as PFGE, mtDNA RFLP, and inter-delta analysis (6,8,48), this S. cerevisiae ecological study used deep sampling and relied on the robustness of the microsatellite marker method (36,(49)(50)(51), performed with 15 loci as microsatellite markers and providing more sensitivity than previous studies. Multilocus microsatellite analysis allowed us to evaluate the genetic diversity of our population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant genetic diversity exists among wine strains of S. cerevisiae whether isolated from the vineyard or winery (Baleiras Couto et al 1996, Briones et al 1996, Gallego et al 2005, Khan et al 2000, Lopes et al 2002, Sabate et al 1998, Schütz and Gafner 1993, Valero et al 2006, Van der Westhuizen et al 2000a, 2000b, Versavaud et al 1995) and the same is true of S. bayanus (Sipiczki 2002). Analysis of over 1,600 isolates of S. cerevisiae from 54 spontaneous fermentations demonstrated the existence of 297 unique strains .…”
Section: Functional Diversity Of Wine Strainsmentioning
confidence: 99%
“…In comparison, interest for the « microbial terroir » of vines (Gilbert et al 2014) is recent and remains less investigated. Valero et al (2007) and Setati et al (2012) were among the first to study the yeast microbiome in vineyards. More recently, on the basis of the analysis of the wine-grape surface microbiome, Bokulich et al (2014) proposed the existence of a non-random microbial terroir as a determining factor of regional variation among vines.…”
Section: Introductionmentioning
confidence: 99%